Imagining emotions in storyworlds: physiological narrated perception and emotional mental imagery - Martínez, María-Angeles (Frontiers in Human Neuroscience, 2024)
Research into narrative experiencing acknowledges the role played by mental imagery in readers' emotional responses and feelings of embodiment (Kuzmičová, 2014). In narratives, mental imagery is frequently evoked through narrated perception, or the textual presentation of "sensory perceptions within what looks like narration" (Pallarés-García, 2012: 170), as in "The silence in the house was complete" (McEwan, 2002: 35). Narrated perception spans the five senses -sight, hearing, smell, touch, and taste (Fludernik, 1996;Shen, 2005); however, little attention has been paid to the narrated description of characters' basic physiological processes, that is, those connected to the invisible systems -respiratory, digestive, cardio-vascular, muscular (Stemmler, 2013) -and their relevance to the mental construction of narrative emotions. This study explores the presentation of fictional characters' physiological processes as a prompt for readers' embodied experience of storyworlds through the metonymic activation of self-relevant emotion schemata (Kövecses, 2000(Kövecses, , 2014)). To this purpose, the presentation of characters' internal physiological processes in two fictional samples of similar length -the ghost story "Harry" (Timperley, 1958) and chapter one in Ewan McEwan's novel Atonement (2002) -is analysed. The findings suggests that these descriptions enrich the imagined nature of narrative emotions through underspecification, and increase opportunities for perceived selfrelevance and engagement.